CRADLE TO CRADLE IN RESIDENTIAL BUILDING: THE FEASIBILITY TO IMPLEMENT THE CRADLE TO CRADLE CONCEPT IN RESIDENTIAL BUILDING - Olga Brommet; Jouke Post (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2019)
Sustainability and Cradle to Cradle are well known concepts for creating buildings. The aim of the article here want to discuss the implementation of Cradle to Cradle in residential building. The method used were literature study and case study. A building is 100% cradle to cradle when every part of the building meets the standard of the C2C principles, includes material health and reutilization, use of renewable energy, water stewardship and social fairness. The result of the study shows that the case study match 89% of cradle to cradle score, which was a good result.